Organophosphate Esters and Polybrominated Diphenyl Ethers in Vehicle Dust: Concentrations, Sources, and Health Risk Assessment - Junji Wang; Jianzai Lin; Xi Zhang; Qinghong Zeng; Zhu Zhu; Siyuan Zhao; Deyan Cao; Meilin Zhu (Toxics)
Background: The primary flame retardants in vehicles, organophosphates (OPEs) and polybrominated diphenyl ethers (PBDEs), volatilize and accumulate in the enclosed vehicle environment, posing potential health risks. Amidst the rising number of vehicles, the scrutiny of persistent organic pollutants like OPEs and PBDEs in vehicles is increasing. This study investigates occupational and nonoccupational population exposure to specific OPEs (TnBP, TBOEP, TEHP, TCEP, TCiPP, TDCiPP, TPhP, EHDPP) and PBDEs (BDE-28, BDE-47, BDE-99, BDE-100, BDE-153, BDE-154, BDE-183, BDE-209) in vehicle dust. Methods: Data on OPEs and PBDEs in vehicle dust were sourced from PubMed and Web of Science. We applied PCA and PMF to identify pollutant sources and assessed health risks using the hazard index (HI) and carcinogenic risk (CR) methods. Monte Carlo simulations were conducted for uncertainty analysis, evaluating variable contributions to the results. Results: The predominant OPE in dust samples was TDCiPP (mean value: 4.34 × 104 ng g−1), and the main PBDE was BDE-209 (mean value: 1.52 × 104 ng g−1). Potential sources of OPEs in vehicle dust include polyvinyl chloride (PVC) upholstery, polyurethane foam (PUF) seats, electronics, carpet wear, hydraulic oil, and plastic wear in the brake system. PBDE sources likely include automotive parts, PVC upholstery, seats, carpets, and electronics. The 90th percentile HI and CR values for occupational and nonoccupational populations exposed to OPEs and PBDEs indicate that the noncarcinogenic and carcinogenic risks are relatively low. A sensitivity analysis showed that the pollutant concentration, time in the vehicle, exposure frequency, and duration significantly influence health risks. Conclusions: The health risks to both occupational and nonoccupational populations from exposure to OPEs and PBDEs in vehicle dust are relatively low.